1984
DOI: 10.1200/jco.1984.2.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic evidence for gene amplification in methotrexate-resistant cells obtained from a patient with ovarian adenocarcinoma.

Abstract: To analyze if methotrexate (MTX) resistance arises from gene amplification in a patient treated clinically with MTX, the cytogenetic and drug sensitivity profile of the tumor colony forming units (TCFUs) from a 58-year-old woman with stage III well-differentiated ovarian serous adenocarcinoma was studied. This patient had not received treatment directed against her tumor for nine months before this study, but had received oral-dose MTX (2.5 mg, twice weekly) for three years for the treatment of psoriasis. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

1985
1985
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…The former type of amplification is much more stable as the latter is lost during cell division. Low-level gene amplification has been identified in tissue specimens from patients with acute lymphoblastic leukemia (ALL) and ovarian cancer (Trent et al, 1984) treated with MTX, indicating that this process plays a role in clinical drug resistance. The low-level amplification detected prior to treatment in human soft-tissue sarcomas suggests that this may be one basis for intrinsic resistance in this disease requiring high-dose therapies (Li et al, 1992b).…”
Section: Alterations In Dhfrmentioning
confidence: 99%
“…The former type of amplification is much more stable as the latter is lost during cell division. Low-level gene amplification has been identified in tissue specimens from patients with acute lymphoblastic leukemia (ALL) and ovarian cancer (Trent et al, 1984) treated with MTX, indicating that this process plays a role in clinical drug resistance. The low-level amplification detected prior to treatment in human soft-tissue sarcomas suggests that this may be one basis for intrinsic resistance in this disease requiring high-dose therapies (Li et al, 1992b).…”
Section: Alterations In Dhfrmentioning
confidence: 99%
“…However, human tumor cells can acquire resistance to Mtx, a phenomenon that has been demonstrated both in vitro and in vivo (5)(6)(7)(8). One well documented mechanism of resistance involves the amplification of a region of the human or rodent genome containing the DHFR gene (5)(6)(7)(8)(9)(10), an event that leads to elevated expression of DHFR, which effectively circumvents the metabolic block produced by this agent.…”
mentioning
confidence: 99%
“…With many drugs, however, resistance in the clinical setting has been shown to evolve by gene amplification , Curt et 01. 1983, Trent et al 1984, Cardman et al 1984. Kellen 1994, Bodey et al 1997, and in these situations the double bind described here may apply.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low drug concentrations facilitated the evolution of resistance. A number of clinical studies have shown three-to sixfold amplification of DHFR genes in patients resistant to MTX, with cancers ranging from leukemia , Cardman et al 1984, to lung cancer (Curt et al 1983) and ovarian cancer (Trent et al 1984).…”
Section: Introductionmentioning
confidence: 99%